Student Learning Outcomes in Civics Education through the Contextual Teaching and Learning Model at Primary School - Sulimaly, Deviana Sherly; Watloly, Aholiab; Ratumanan, Stelie Dorce (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Low student learning outcomes in civics education often stem from conventional teaching methods that fail to connect classroom material with real-world experiences, as observed in primary school. Therefore, this study intends to analyze the application of the Contextual Teaching and Learning (CTL) model in improving student learning outcomes regarding the implementation of rules at school and in the surrounding environment. The research employed Classroom Action Research (CAR) with a quantitative approach, conducted at Primary School Wakarleli, Southwest Maluku. Data was gathered via interviews, observations, and documentation to verify the efficacy of the CTL model's implementation. The findings indicate that the CTL model significantly enhances student performance. In Cycle I, student learning outcomes reached only 52.94%; however, after refining the instructional approach in Cycle II, the success rate increased to 100%. This study contributes to the field of primary education by providing empirical evidence that the CTL model is an effective strategy for teaching civics, as it helps students bridge the gap between theoretical knowledge and practical application in their daily lives.